Effect of dietary concentrate to forage ratios on ruminal bacterial and anaerobic fungal populations of cashmere goats. (October 2019) - Han, Xufeng; Li, Bibo; Wang, Xiaolong; Chen, Yulin; Yang, Yuxin
Abstract: The rumen contains a highly complex microbial ecosystem that plays an important role in converting solar energy in plants into nutrients for ruminants and generates animal food products, such as meat and milk for humans. Therefore, understanding the effect of the dietary concentrate to forage (C:F) ratio on ruminal microbiota is of great significance for the growth and development of ruminants. In this study, changes in the ruminal bacterial and anaerobic fungal populations of Shaanbei white-cashmere (SWC) goats that were reared under different dietary C:F ratios were evaluated by high-throughput sequencing analysis. It was found that dietary C:F ratio has a significant impact on the composition of the ruminal bacteria in SWC goats. The levels of Actinobacteria and Proteobacteria were significantly increased ( P < 0.05), whereas the level of Bacteroidetes was significantly decreased when the proportion of dietary concentrate was increased ( P < 0.05); as the proportion of dietary concentrate increased, Prevotella, Selenomonas, and Treponema were significantly increased ( P < 0.05), whereas Oscillospira and Succiniclasticum were significantly reduced ( P < 0.05). Furthermore, different dietary C:F ratios significantly affected the composition of anaerobic fungi in SWC goats. As the proportion of dietary concentrate increased, Ascomycota, Basidiomycota, and Zygomycota were significantly increased ( P < 0.05), while Neocallimastigomycota was significantly reduced ( P < 0.05); the levels of Alternaria, Aspergillus, Neocallimastix, Orpinomyces, Piromyces, and Stachybotrys were significantly increased, while those of Candida, Penicillium, and Trichosporon were significantly decreased when the proportion of dietary concentrate increased ( P < 0.05). These findings will help us to better understand the changes in ruminal bacterial and anaerobic fungal populations of SWC goats under different dietary C:F ratios, which could provide a theoretical basis for microecological regulation of SWC goats. Highlights: The different dietary C:F ratios significantly influenced the composition of bacteria and anaerobic fungi in the rumen. Prevotella was the most abundant bacterial genus in the rumen of goats raised under different dietary C:F ratios. Neocallimastix was most abundant in the C30 group, while Candida was most abundant in the C50 and C70 groups. The population of Ruminococcu s and Butyrivibrio were significantly decreased when the dietary C:F ratio was increased.